A STUDY ON CONSUMER BUYING BEHAVIOR TOWARDS GOLD JEWELLERY - SPECIAL REFERENCE TO COIMBATORE CITY - P. Sudhaker; Madhavedi, Dr. Sudhakar; Makwane, Trupti; Padamati, Sangeetha (International Journal of Psychosocial Rehabilitation, 2019)
The purpose of this study is to look at the shopping habits of Coimbatore residents when it comes to gold jewellery. The information was gathered using survey methodologies and a questionnaire with 120 respondents. Simple percentage analysis and likert scale analysis were employed in this project. Customers are willing to acquire gold ornaments, according to the findings of the study. The majority of customers are interested in Gold Loan. Only a discount on schemes is what the customer expects. These are some of the study’s findings. As a result, the study showed that consumers are satisfied with their gold jewellery purchasing habits.